A Formal Model of Trust Based on Outcomes - Bhattacharya, Rajeev R.; Devinney, Timothy M.; Pillutla, Madan M. (Academy of Management Review, 1998)
The study of trust has occupied scholars from a number of disciplines, who have made limited attempts at integrating the different streams. One reason for lack of integration is that no clear definition of trust exists. In this article we grapple with this issue by going back to first principles to derive a mathematically precise and statistically rigorous definition of trust. In giving a rigorous meaning of trust, we also capture the key elements of the concept as highlighted by various disciplinary lenses. Our definition of trust, although rationally based, is consistent with many of the findings of earlier behavioral and sociological research. Its contribution is in adding precision and richness to our understanding of how trust is created and maintained in various social and economic interactions.